3D hierarchical porous cobalt monoxide nanoplates with a book-like structure derived from Co(CO3)0.5(OH)·0.11H2O: two-steps oriented attachment and high-performance asymmetric supercapacitors. (24th October 2017) - Xiao, Yuanhua; Zhao, Xiaobing; Jin, Qingxian; Su, Dangcheng; Wang, Xuezhao; Wu, Shide; Zhou, Liming; Fang, Shaoming
Abstract: 3D Hierarchical porous cobalt monoxide (CoO) nanoplates with a book-like structure derive from Co(CO3 )0.5 (OH)·0.11H2 O by a two-steps oriented attachment mechanism in the solvothermal process. Firstly, nanoplates are formed by oriented attachment of nanorods. Secondly, new nanoplates could be generated on the old nanoplates by a sloped oriented attachment of nanorods with the based nanoplates shape into a 3D hierarchical book-like structure. The CoO nanoplates show superior specific capacitance about 1221.7 F g −1 at 1 A g −1 to most of the Co-based supercapacitor materials up to date. An asymmetric supercapacitor (ASC) based on positive electrode CoO and negative electrode active carbon (AC) exhibits an excellent energy density of 50.1 Wh kg −1 at a power density of 589 W kg −1 and gets a satisfactory cycling stability (86.3% of its initial capacitance retention at 10 A g −1 over 10 000 cycles).